MULTI-PERIOD SUPPLY CHAIN COORDINATION USING TRADE PROMOTION: COMPLEMENTARY SLACKNESS APPROACH - Tantiwattanakul, Phattarasaya; Dumrongsiri, Aussadavut (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
In this paper, a two-level supply chain network with a single manufacturer supplying a single product to a single retailer is studied. This research uses a trade promotion strategy to coordinate the supply chain by finding the optimal pre-announced multi-period wholesale prices that can induce the retailer’s decentralized decisions to be the same as the retailer’s centralized decisions with the minimum total cost for the supply chain. The manufacturer makes production, inventory, and wholesale price decisions. The retailer makes ordering and inventory decisions. A procedure is proposed to determine optimal wholesale prices to pre-announce in each period to the retailer, coordinating the supply chain using complementary slackness conditions. The results show the coordination benefits for a supply chain when the setup or reorder cost is high but the average demand is low. Finally, the performance of the proposed method is compared with the performance of the “Every Day Low Price” wholesale price policy.